A politicidade da educação a partir da experiência de uma docente de sociologia - Chaves, Silvania Maria (Universidade Federal de São Carlos, 2017)
This job had as objective Reflect and reaffirm Education as a political act and democracy. The studies conducted evidence we are living in times of setback regression, marked by loss of rights and by the productions of impotence and suffering: the capitalist Western rationality has produced, in this way, atomized, fragile individuals and the idea that changing reality is impossible. Although this context contributes to the construction of conformed subjectivities, we perceive History as a possibility in which men and women are subjects of change and resistance in midst of forces that act, simultaneously, in a regulatory and emancipatory manner. From the perspective of education as a possibility, as a result of historical time, we share powerful experiences, loaded with how to understand education as a political act, held in the sociology classes of the State School Aggêo Pereira do Amaral, located in Sorocaba, in the interior of the State of São Paulo, considering that they are tools for confronting the dynamics of servitude, prejudice, racism, fascism and machismo, intricate in the daily microrelations. Based on the theoretical dialogues and the narrated experiences, we affirm that pedagogical practices based on solidarity, dialogue and cooperation open doors to the creation of emancipatory sociability’s and constitute seeds for the construction of a world did from humanized and democratic relations. The educational processes and ongoing resistance movements shared in this research fuel the hope that another reality is possible and that social transformation will occur through collective action. In a scenario that has denied politics, we reaffirm it as an extension of life as a power.
The politics of educatgion from the experience of a teacher of sociology
Keywords: Politicidade da educação; Resistência; Ensino de Sociologia; Politics of education; Resistance; Teaching Sociology; Sociologia - Estudo e ensino; Sociology - Study and teaching; Professores - Formação; Teachers - In-service training; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM